2019
DOI: 10.3390/rs11020113
|View full text |Cite
|
Sign up to set email alerts
|

Ice-Gouging Topography of the Exposed Aral Sea Bed

Abstract: Ice gouging, or scouring, i.e., ice impact on the seabed, is a well-studied phenomenon in high-latitude seas. In the mid-latitudes, it remains one of the major geomorphic processes in freezing seas and large lakes. Research efforts concerning its patterns, drivers and intensity are scarce, and include aerial and geophysical studies of ice scours in the Northern Caspian Sea. This study aims to explain the origin of the recently discovered linear landforms on the exposed former Aral Sea bottom using remotely sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…On the saline soil of the seabed, show on the map the vegetation that is planted for cleaner air, which is necessary for the inhabitants of the Aral Sea region. Along with this, on the previously drained seabed, it was found that next to and close to these plantings, self-overgrowth covered another 200 thousand hectares [4]. Nature itself is trying to recover on the dried bottom.…”
Section: Icecae 2024mentioning
confidence: 86%
See 2 more Smart Citations
“…On the saline soil of the seabed, show on the map the vegetation that is planted for cleaner air, which is necessary for the inhabitants of the Aral Sea region. Along with this, on the previously drained seabed, it was found that next to and close to these plantings, self-overgrowth covered another 200 thousand hectares [4]. Nature itself is trying to recover on the dried bottom.…”
Section: Icecae 2024mentioning
confidence: 86%
“…A large soda plant was built in the Kungrad area. On the dried bottom, many drilling units operate to drill wells for natural gas production [4]. All these developments and new industrial plants must be shown with symbols on maps.…”
Section: Icecae 2024mentioning
confidence: 99%
See 1 more Smart Citation
“…Bukharitsin (1984) showed that the sea level decrease in 1974-1980 led to the displacement of the zone most intense ridging to the deeper zone and southward from the coast. In similar conditions of sea level drop at the Aral Sea Maznev et al (2019) showed the offset of ice features and the most intensive ice gouging area away from the initial coastline. The present study shows that sea level rise by 1 m leads to changes in stamukhi locations.…”
Section: Table 3 Long-term Changes Of Temperature and Ice Conditionsmentioning
confidence: 87%
“…A S an important acoustic sensor device for ocean exploration, side-scan sonar (SSS) is widely used in seabed topography surveying [1], shipwreck salvage [2], underwater archaeology [3], etc. For SSS image processing, many Corresponding author:wangzhen4013@163.com Zhen Wang and Shanwen Zhang are with the School of Information Engineering, Xijing University, Xi'an 710123, China (e-mail: wangzhen4013@163.com, wjdw716@163.com) Buhong Wang is with the School of Information and Navigation, Air Force Engineering University, Xian 710082, China (e-mail: wbhgroup@163.com) Chuanlei Zhang is with the School of Artificial Intelligence, Tianjin University of Science and Technology, Tianjin, China, 300457 (email:97313114@tust.edu.cn) [16].…”
Section: Introductionmentioning
confidence: 99%